Penerapan Terapi Murottal Al-Qur’an Surat Al-Kahfi dalam Asuhan Keperawatan Pasien Hipertensi dengan Masalah Ansietas: Penelitian - Femilya Indriastiani Sari; Tiara Fatma Pratiwi; Leo Yosdimyati Romli; Arif Wijaya (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Anxiety can occur in patients with hypertension. A patient with hypertension may experience anxiety because hypertension tends to require relatively long-term treatment, carries a risk of complications, and can shorten life expectancy. The purpose of this study was to identify nursing care for elderly patients with hypertension who have anxiety-related nursing problems. Methods this study used a case study approach with two hypertensive patients with anxiety nursing problems as subjects. Nursing interventions were carried out for 3 days using Murottal Al-qur'an therapy from Surah Al-Kahfi. Data collection was obtained through interviews, observation, and documentation. The instrument used was a medical-surgical nursing care format. The results of this study showed that the assessment found similarities in both patients, namely that they were worried about their illness. The nursing diagnosis found the main problem to be anxiety in both patients. The researcher adjusted the intervention according to the SLKI and SIKI books. The implementation used Al-Quran Murottal therapy from Surah Al-Kahfi, which was carried out for 3 days. and in the evaluation, the problem was resolved on the third day with a decrease in anxiety levels. The administration of Al-Kahfi Quran recitation therapy was proven to reduce anxiety in hypertensive patients and can be applied to other elderly hypertensive patients.